Model Prediksi Kegagalan Bank Pasca Merger Berdasarkan Nilai Rasio Keuangan - Theresia Gunawan (Business Administration Department - Universitas Katolik Parahyangan, 2008)
By merging banks with one another, the government hopes to improve the general condition or quality of banks. However, after these mergers there are twenty banks that have been liquidated, and only nineteen remain operation. The aim of this paper is to construct a model in order to predict the failure of merged banks in Indonesia, based on financial ratios. The object of research consists of the financial ratios of either liquidated or successful ones. The data are collected from a published financial reports of those banks which have been audited and processed as financial ratios. These financial ratios are analysed by way of logistic regression. The research hypothesis proposed is that financial ratios can be turned into prediction models to establish the degree to which mergers have failed in Indonesia. The results show that the financial standard of performance of failed banks is indeed inferior to that of successful ones The results from the statistical test also indicate that the combination of RR and ROA financial ratios are the most significant ones to pass the compatibility or ”proper and fitness” test to predict the extent of failure of mergers between banks in Indonesia. The outcome of research may be exploited by society at large, observers of the banking world, and Bank Indonesia by way of an early warning system concerning the failure of mergers between banks in Indonesia. Keywords: Financial ratios, banking performance analysis, merger